1975
DOI: 10.1002/pssa.2210310130
|View full text |Cite
|
Sign up to set email alerts
|

Heat flow rectification in inhomogeneous GaAs

Abstract: Thermal conductivity measurements of a monocrystalline nonhomogeneous GaAs sample exhibit different conductivities with respect to the direction of heat flow across the sample. It is found that the same applied external temperature gradient causes two different distributions of the effective thermal conductivity coefficient, depending on the two opposite directions of heat flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…A certain amount of thermal rectification can be achieved between two bulk materials with strongly different thermal conductivity dependence on temperature [142]. This is in fact a classical Fourier law effect, first observed in the 1970s [143,144] and recently reexamined by Dames [142] and Kobayashi et al [145]. As shown in Fig.…”
Section: Thermal Rectificationmentioning
confidence: 84%
“…A certain amount of thermal rectification can be achieved between two bulk materials with strongly different thermal conductivity dependence on temperature [142]. This is in fact a classical Fourier law effect, first observed in the 1970s [143,144] and recently reexamined by Dames [142] and Kobayashi et al [145]. As shown in Fig.…”
Section: Thermal Rectificationmentioning
confidence: 84%
“…material A has low thermal conductivity at low temperature and high thermal conductivity at high temperature while material B is the opposite). This mechanism was initially proposed by Marucha et al when they performed experiments on inhomogeneous GaAs and found a directional dependence of the thermal conductivity [28]. Marucha et al later analyzed the system using the one-dimensional Fourier equation and found that this temperature dependence of the thermal conductivity would result in thermal rectification [29].…”
Section: Temperature Dependence Of Thermal Conductivity At Interfacesmentioning
confidence: 89%
“…[ 1 ] Thermal diodes are desirable for the smart thermal management of electronics packaging [ 2–4 ] or spacecraft, [ 5,6 ] as they can effectively dump onboard heat while also shielding from external heat sources. The effectiveness of a thermal diode is quantified by its diodicity (also known as the rectification coefficient), which compares the effective thermal conductivity in the forward mode ( k f ) to that in the reverse mode ( k r ) [ 7 ] : η=kfkrkr …”
Section: Introductionmentioning
confidence: 99%